Development of Interactive Multimedia Computer-Assisted Learning Method for Empowering Breastfeeding Mothers in Family Learning Centers - Susilawati, Dewi; Nilakesuma, Nur Fajdri; Musharyadi, Feri (jitek, 2025)
The low achievement of exclusive breastfeeding is a public health problem worldwide. Exclusive breastfeeding coverage in Indonesia in 2023 was recorded at only 67.94%, down from 2022. One contributing factor is the lack of support for breastfeeding mothers. Various strategies can be implemented to enhance family involvement, one of which is education through a family center learning approach. One method that can be used in providing education is the computer assisted learning (CAL) method. Develop interactive multimedia with the CAL method that can be used in family center learning to empower breastfeeding mothers. ADDIE model, to produce CAL-based multimedia applications. The method used to collect data was questionnaires and data analysis using descriptive statistics. Computer Assisted Learning-based multimedia design named "Successful Family-Based Exclusive Breastfeeding" with a web page https://sites.google.com/view/asi-ekslusif. The results of the trial to experts were all experts stated "Worth using" with an average score of 3.64 material experts and 3.8 media experts. The results of the trial to the breastfeeding mother's family were the average appearance aspect of 3.8 which means very feasible, the average material presentation aspect of 3.9 which means very feasible and the average benefit aspect of 3.8 which means very feasible. Computer Assisted Learning-based multimedia design named "Successful Family-Based Exclusive Breastfeeding" is suitable for use in family center learning to empower breastfeeding mothers.